Pengaruh Takaran Biochar Kotoran Ternak Kambing Diperkaya Kompos dalam Media Tanam terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) pada Tanah Entisol - Nofrida Moru (Fakultas Pertanian, Universitas Timor, 2021)
The purpose of this study was to determine the effect of the Biochar dose of Goat Manure Enriched with Compost in the Media on the Growth of Mustard Plants (Brassica juncea L.) in Entisol Soil. This research was carried out from November to December 2020. The experimental garden of the Faculty of Agriculture, University of Timor, Sasi Village, Kefamenanu city sub-district, North Central Timor Regency. This research design used a single faktor completely randomized design (CRD), namely biochar goat manure + compost which was repeated 4 times so that there were 44 experimental pots. 0g, 50g, 100g, 150g, 200g, 250g, 300g, 350g, 400g, 450g, 500g. Biochar Treatment of Goat Manure Enriched with Compost Gives Significant Effects on Plant Growth and Yield and on All Observation Parameters Except Plant Height 14.21 DAP, Number of Leaves 14.21 DAP, And Non-Economic Fresh Weight. Dosage of Biochar Goat Manure Enriched Compost 450G With The Highest Dosage To Produce The Growth And Yield Of Mustard Plants.